(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
Using the facts the authors demonstrate that antonymity is the main means of expression of contrast on the structural-semantic and functional levels. The usage of total and contextual antonyms in the prose by V.Shevchuck is reasoned with peculiarities of writer’s world outlook and his individual manner of language creation.